2019
DOI: 10.1200/jgo.18.00208
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Features of Young Versus Older Patients With Breast Cancer at a Single Pakistani Institution and a Comparison With a National US Database

Abstract: PURPOSE The age at which women present with breast cancer varies widely among nations, and breast cancer may behave differently in younger women. Differences in clinicopathological characteristics based on age have not been well characterized in Pakistani patients with breast cancer. METHODS We conducted a retrospective review of patients with symptoms of breast cancer presenting to Aga Khan University Hospital (AKUH), a large tertiary care center in Pakistan, between 2001 and 2010; we compared young (≤ 40 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 17 publications
3
26
2
Order By: Relevance
“…These discrepant observations may be attributed to the predominant aggressive tumor biology of our TNBC cohort where only 6% of the patient population was diagnosed with stage I disease and about 40% of the patients had axillary LN metastasis at initial diagnosis. The plausible factors associated with aggressive tumor biology among Pakistani women compared to Western, Asian, and African cohorts require further genetic and epidemiological studies ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…These discrepant observations may be attributed to the predominant aggressive tumor biology of our TNBC cohort where only 6% of the patient population was diagnosed with stage I disease and about 40% of the patients had axillary LN metastasis at initial diagnosis. The plausible factors associated with aggressive tumor biology among Pakistani women compared to Western, Asian, and African cohorts require further genetic and epidemiological studies ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is comparable to the study performed in Pakistan and India, where 56.8%, 47.6%, and 58.5%cases were ≤50 years of age, respectively (Table 2 ). Zeeshan et al found that 27.4% of breast cancer patients were even younger than 40years [ 7 , 11 - 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, over 21% of all breast cancers occurred in women under 40 years of age. In other studies, percentages of breast cancer under 40 years of age have ranged from 17.2-27.4% [14,15]. A recent study from the United States argued that although approximately two third of women with breast cancer under 50 years of age are not high risk, women should receive annual mammograms from age 40 years since low risk does not confer protection [16].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from the United States argued that although approximately two third of women with breast cancer under 50 years of age are not high risk, women should receive annual mammograms from age 40 years since low risk does not confer protection [16]. A recent study from a single institution in Pakistan which compared its ndings with a national US database found that breast cancer in Pakistani patients under 40 years of age was even more aggressive and advanced than breast cancer in a similar age group in the United States [15].…”
Section: Discussionmentioning
confidence: 99%